ROLE OF ASSESSSMENT FOR RETREATMENT WITH TRANSARTERIAL CHEMOEMBOLIZATION SCORE IN DECISION OF RETREATMENT WITH TRANS-ARTERIAL CHEMO-EMBOLIZATION SESSIONS IN PATIENTS WITH HEPATOCELLULAR CARCINOMA - Abbasi, Anwar Hussain; Abid, Shahab; haq, Tanveer; awan, Safia (Journal of Ayub Medical College Abbottabad, 2017)
Background: The objective behind this study was to determine that Assessment for Re-treatment with Transarterial chemoembolization (ART) score is really applicable in patients with hepatocellular carcinoma. Methods: A cross sectional observational study was conducted on all patients with hepatocellular carcinoma of intermediate stage and undergone ‰¥2 Transarterial chemoembolization. ART score was assessed before and after each session of Transarterial chemoembolization. Multi-logistic regression analysis was performed to compare the final outcome of patients with ART score of ‰¥2.5 into groups with two and more than two Trans-arterial chemo-embolization sessions. Results: A total of 100 HCC patients were recruited for final analysis. Our study participants consisted of total 100 HCC patients. Mean Child Pugh score was 6.1±0.95. In our study, most of the study participants (n=63) had ART score of less than 1.5 as compared to ART score >2.5 (n=37). A significant proportion of patients with ART score of <1.5 prior to second Trans-arterial chemo-embolization had better median survival as compared to patients with ART score of >2.5, p-value<0.001. Patients with ART score of more than 2.5 did not show any survival benefit after having 3rd or 4th Trans-arterial chemo-embolization session, p=0.47. Conclusions: Our study findings suggest that those HCC patients who receive multiple sessions of TACE with a low ART score have more favourable outcomes with increased survival rate. Keywords: Hepatocellular carcinoma; Child Pugh Classification; MELD score; ART score